Determinants of pain, anxiety and patient satisfaction during intravenous injection: a cross-sectional study - Yildiz, Guzel Nur; Yuce Basaran, Hanim Duru; Yavuz, Burak; Kocyigit, Dilara; Koc, Gamze; Ciftci, Bahar (Bmj Publishing Group, 2026)
Background Intravenous injection is one of the most frequently performed invasive nursing procedures in hospitals. However, patients may experience pain and anxiety during this procedure, which can affect patient satisfaction. Objective The aim of this study was to determine the levels of pain, anxiety and satisfaction in patients undergoing intravenous injection and to examine the sociodemographic, clinical and procedural factors affecting these levels. Methods A descriptive, cross-sectional study was conducted between August and November 2025 in the emergency departments of Atat & uuml;rk University Research Hospital, a large tertiary care university hospital. This single-centre study was carried out in a high-volume emergency department that provides 24-hour services to a diverse patient population. A total of 405 patients who received intravenous injections and agreed to participate in the study were included. Data were collected using an Information Form, Visual Analogue Scale (VAS) for pain, VAS for anxiety and Post-Injection Satisfaction Scale. Descriptive statistics, t-tests, analysis of variance, correlation analyses and multiple regression analyses were used to analyse the data. Results The mean pain VAS score for patients was 4.39 +/- 2.33, the mean anxiety VAS score was 4.42 +/- 2.14 and the mean Post-Injection Satisfaction Scale score was 3.51 +/- 0.77, indicating moderate levels of pain and anxiety on a 0-10 VAS. Women were found to have significantly higher levels of pain and anxiety than men (p<0.05). Low educational level, chronic disease, poorer perceived general health, negative intravenous experience, frequent injections, low pain tolerance and prolonged pain were associated with higher pain and anxiety levels and lower satisfaction levels (p<0.05). A strong positive correlation was found between pain and anxiety (r=0.656, p<0.05), while a negative correlation was found between pain, anxiety and satisfaction (p<0.05). Multiple regression analysis showed that lower pain tolerance and longer pain duration were among the most clinically relevant variables associated with higher pain and anxiety levels, particularly pain tolerance and pain duration, together with perceived general health status and procedure-related variables. Conclusion It was found that patients experienced moderate pain and anxiety during intravenous injection and that this situation negatively affected patient satisfaction. The results indicate that individualised nursing approaches in intravenous injection practices and the implementation of pharmacological and non-pharmacological interventions aimed at reducing pain and anxiety may increase patient satisfaction.
Keywords: Patient Satisfaction; Nurses; Patient Care Management